Teaching Vocabulary for Elementary School Students - Permana, I Gede Yoga (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
The present study investigated the teaching strategies to develop elementary students’ vocabulary. In conducting the study, a literature review was conducted. The findings showed that in teaching vocabulary for elementary school, teachers are required to use interactive media such picture, game, and song. Literature studies also found that interactive media greatly influences students’ motivation and engagement toward vocabulary learning process. Teachers are encouraged to use interactive teaching media in developing students’ vocabulary. Discussions and suggestions of study are further presented.